Unified Model for Axial Bearing Capacity of Concrete-Filled Steel Tubular Circular Columns Based on Hoek–Brown Failure Criterion - Ziao Zhou (Buildings, 2023)
Concrete-filled steel tubular (CFST) composite columns can overcome the brittleness of concrete and improve the plastic deformation ability of concrete, thus improving its strength and deformation ability. At present, most of the published models for predicting the axial bearing capacity of CFST columns are empirical models based on the nonlinear fitting of experimental data, which has some limitations on the application of the models. Therefore, to establish a new unified theoretical model, a new ultimate compressive strength of core concrete was established by the Hoek–Brown failure criterion, and the conversion formula between the cube and cylinder compressive strength was also established in this paper. At the same time, the strength-reduction coefficient influenced by the slenderness ratio was also established. The newly established unified model can predict the axial bearing capacity of CFST columns with different steel types, concrete types, slenderness ratios, diameter-to-thickness ratios, and cross-sectional dimensions. At the same time, the newly established unified model can be applied to a wider range of test parameters. To determine the parameters in the proposed model and assess the models, a total of 798 test data were collected. Based on the test database, the existing models and the proposed model were evaluated. The results show that the proposed model has very high accuracy in predicting the test results of CFST short and long columns, and the average value (AV) and integral absolute error (IAE) are 1.012 and 0.094, respectively. In addition, the model proposed in this paper also has high accuracy in predicting the axial bearing capacity of CFST columns under high temperatures.